1991
DOI: 10.1300/j069v10n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Neurochemical Studies in Diazepam-Sensitive and Resistant Mice

Abstract: Benzodiazepine (BZ) effects include anxiolyis, sedation, seizure protection, and muscle relaxation; the mechanisms underlying these various effects are not understood. We have recently used the rotarod test in conjunction with selective breeding techniques to develop lines of mice which are diazepam-sensitive (DS) and diazepam-resistant (DR). We review the general methods of selective breeding, along with a description of the DS/DR selection study, and then describe a variety of behavioral and neurochemical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The lack of differences between the blank group and the vehicle group indicates that the saline injection did not influence our results. The positive control group confirms the quality of our model because the data are in according to the previous results[ 43 ] observed in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…The lack of differences between the blank group and the vehicle group indicates that the saline injection did not influence our results. The positive control group confirms the quality of our model because the data are in according to the previous results[ 43 ] observed in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the data suggest that insensitivity to at least some of the effects of benzodiazepines may be coselected when breeding for psychological properties, but the logic of these effects is elusive. It has been demonstrated that insensitivity (and sensitivity) to at least one benzodiazepine, diazepam, can itself be selectively bred for in mice (Gallaher & Gionet, 1988; Gallaher, Gionet, & Feller, 1991; Gallaher, Hollister, Gionet, & Crabbe, 1987). The diazepam-resistant mice were also more resistant to sedative effects of ethanol, phenobarbital, lorazepam, and alprazolam than the diazepam-sensitive mice.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding the GABA A receptor mechanisms underlying specific motor-impairing effects such as ataxia and myorelaxation would clearly benefit drug discovery efforts geared toward anxiolytic development. In rodents, BZ-induced ataxia is often measured using the rotarod test (Gallaher et al 1991; Griebel et al 1999b), while the myorelaxant effects of BZs are typically assessed using a test of grip strength (Griebel et al 1999a; Crestani et al 2001; Bach-Rojecky and Samarzija 2005). In non-human primates, observational procedures have been used to evaluate the effects of BZs on these measures.…”
mentioning
confidence: 99%